2020
DOI: 10.1039/c9ew01016e
|View full text |Cite
|
Sign up to set email alerts
|

Ferric tannate photothermal material for efficient water distillation

Abstract: Ferric tannate is used as a photothermal material and integrated with a polymer membrane by atomic layer deposition for solar water distillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…accessible to more people), robust, efficient and stand-alone (where no moving parts are present) desalination technologies able to operate even in emergency conditions have been recently designed and studied in literature. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The attention has been mainly focused on the study and design of new nano-structured materials and smart structures able to improve the solar-to-vapour conversion and the energy management. 13,[22][23][24][25][26][27][28][29] In 2018 some of the authors proposed a solar passive and multistage distiller 5 able to achieve performance beyond the thermodynamic limit of a single stage device, by recovering the latent heat of condensation.…”
Section: Introductionmentioning
confidence: 99%
“…accessible to more people), robust, efficient and stand-alone (where no moving parts are present) desalination technologies able to operate even in emergency conditions have been recently designed and studied in literature. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The attention has been mainly focused on the study and design of new nano-structured materials and smart structures able to improve the solar-to-vapour conversion and the energy management. 13,[22][23][24][25][26][27][28][29] In 2018 some of the authors proposed a solar passive and multistage distiller 5 able to achieve performance beyond the thermodynamic limit of a single stage device, by recovering the latent heat of condensation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,3,4 ] A variety of solar‐absorbing materials are developed and explored currently, such as low‐dimensional carbon nanomaterials, hydrogel‐based composites, covalent organic frameworks, organic/inorganic composite complex and plasmonic particles. [ 1,3,4,14–18 ] In comparison, it can be found that the materials with nearly 100% absorption of the full‐spectrum solar radiation did not achieve the same evaporation rate (ER) and some even exhibited a lower ER than those with the inferior absorbance. [ 15,19–24 ] This has been attributed to the differences of heat losses, particularly induced by conduction loss to the photothermal material itself.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Zhang et al adopted the filtration/ALD coating method to realize black ferric tannate@TiO 2 coatings (Figure 11B). 83 The optimized as-fabricated membranes demonstrated a water evaporation rate of 0.441 kg À1 m À2 after 20 min operation. The evaporation efficiency in this case is ca.…”
Section: Solar Steam Generationmentioning
confidence: 96%
“…Similarly, Zhang et al reported that black ferric tannate-based photothermal coating could be robustly adhered through stepwise filtration coating and ALD coating (Figure 6G). 83 There are few reports of similar multifunction integration cases during SIS processes, which is a ripe area for future investigation.…”
Section: Growth With An Intermediate Layermentioning
confidence: 99%